Desenvolvimento da ferramenta computacional Fratcond, para modelagem de aquíferos fraturados, utilizando redes de fraturas discretas e condutos equivalentes - Reis, Alan (2018)
The Serra Geral Formation, in the South and Southeast Brazilian regions, and the Crystalline Basin, in the Northeast Brazilian region, are examples of geological structures that shelts fractured aquifers, where there are tubular wells with the purpose of public supply and for use in agricultural and industrial activities. Despite this ordinary use, flow modelling of this aquifer type is poorly researched in Brazil. Different representation forms of fractured aquifers are already seen in the international literature. One of these is the discrete fracture network model (DFN), which aims to accurately represent the fractured rocky environment, detailing the discontinuities location and geometry, where water tends to transit more easily. The modeling of discrete fracture networks usually requires the solution of the flow equations in three-dimensional networks formed by discs, regular polygons or by networks of 1D equivalent pipes. The latter model presents computational advantage, by reducing the quantity of variables to be determined and adequately representing the phenomenon studied, both in terms of flow and transport. In this sense, this work has as objective to present the computational tool FratCond, developed in MATLAB, for fractured aquifers modeling. This tool is able to stochastically generate a network of discrete fractures, based on statistical data of the main descriptive variables of the fractured system under analysis. The hydraulic modeling, in terms of steady flow, uses the concept of 1D equivalent pipes, obtained after the fractures generation, and allowing to obtain the total pressure and the flow rates in the discontinuities. The results, obtained from a hypothetical example, show the various potentialities of the developed tool, allowing a complete analysis of the fractured aquifers, both in terms of geometry and hydraulic characteristics.